BEING CUNNINGHAM'S WOMEN: The Portrayal Of Women In Michael Cunningham's The Hours - Saraswati, Citra Dewi (2013)
This present study entitled Being Cunningham's Women: The Portrayal of Women in Michael Cunningham's The Hours is aimed to unearth the way in which Michael Cunningham, as a male author, portrays women in the novel The Hours. This study employs qualitative descriptive method coupled with textual analysis approach. The study proves that the way Cunningham portrays women in The Hours is different from those of most canonical male authors who make women insignificant in their fictions. It can be seen from the portrayal of women as the ones who unconfident and exhausted in domestic sphere yet powerful enough to make their own decision to liberate themselves from the exhaustion caused by their life. With the benefit of stream of consciousness method, Cunningham has successfully portrayed women's experience and their situation accurately while, at the same time, diffusing liberal feminism value in his work. Keywords: feminism, liberal feminism, portrayal, stream of consciousness